Toward an integrative discourse on climate change. Issue 1 (March 2019) - O'Brien, Karen; Leichenko, Robin
Harriet Bulkeley's article raises some of the persistent challenges of integrating social science perspectives into climate change research. In this commentary, we consider a broader and deeper approach to integration that introduces multiple entry points for engaging with climate change research, education, and training. We argue that an integrative discourse is already emerging and discuss the potential role and implications for human geography.